Headache disorders and risk of stroke: A register-linked HUNT study - Samita Giri; Erling Tronvik; Håvard Dalen; Hanne Ellekjær; Alexander Olsen; Knut Hagen (SAGE Publishing, 2024)
Background Many studies have found that migraine with aura (MA) is a risk factor of stroke, but the relationship between stroke and migraine without aura and tension-type headache is unclear. The aim of this study was to investigate whether primary headache disorders, including subtypes of migraine, increase the risk of ischemic or hemorrhagic stroke. Methods This large population-based 13-year follow-up study used baseline headache data from the third Trøndelag Health Study (HUNT3) performed between 2006 and 2008. The HUNT3 headache data were linked to the Norwegian National Stroke Register that includes stroke diagnoses recorded from 2013 until December 2021. The association between stroke and headache status was investigated in individuals aged ≥20 years without stroke at baseline. Prospective associations were evaluated using multivariable Cox proportional hazard models with 95% confidence intervals. Separate sub-group analyses by age and sex were performed. Results Among 37,364 included participants, 50% were younger than 55 years. A total of 1095 (2.9%) developed stroke after a median of 9 years. In the multi-adjusted model, reporting MA at baseline was associated with increased risk of stroke at follow-up (HR 1.59, 95% CI 1.14-2.21) compared with those without headache. The increased risk of stroke was most evident among individuals <55 years with MA (HR 2.18, 95% CI 1.24-3.82) and among women (HR 1.70, 95% CI 1.12-2.59). Migraine without aura (MO), tension-type headache (TTH) and unclassified headaches were not associated with increased risk of stroke. Conclusions During 15 years of follow-up, individuals with MA were more likely to suffer from stroke compared to those without headache. The relationship with MA was even stronger in women, and for young individuals aged <55 years. Individuals with MO or TTH were not associated with increased risk of stroke.